Petropolitics Petroleum Development, Markets and Regulations, Alberta as an Illustrative History - MacFadyen, Alan (Energy, Ecology and the Environment, 2014)
The importance of energy to the functioning of any economy has meant that energy industries are amongst the most regulated of industries. What might appear to be purely private decisions are made within a complex and evolving web of government regulations. Petropolitics: Petroleum Development, Markets and Regulations, Alberta as an Illustrative History provides an economic history of the petroleum industry in Alberta as well as a detailed analysis of the operation of the markets for Alberta oil and natural gas, and the main governmental regulations (apart from environmental regulations) faced by the industry. The tools used within this study are applicable to oil and gas industries throughout the world. Winner, 2014 Book of the Year, Petroleum History Society